Bonjour,
a) 3 (5x+7)-4 (2x-5)=0
15x + 21 - 8x + 20 = 0
15x - 8x = - 21 - 20
7x = - 41
x = - 41/7
b) Il manque quelque chose
c) (2x+5)(x -2)-(2x+5)(4x -4)=0
2x²- 4x + 5x - 10 - (8x² - 8x + 20x - 20) = 0
2x² - 4x + 5x - 10 - 8x² + 8x - 20x + 20 = 0
2x² - 8x² - 4x - 20x + 5x + 8x - 10 + 20 = 0
- 6x² - 11x + 10 = 0
(- 5 - 2x) (3x - 2) = 0
- 5 - 2x = 0 ou 3x - 2 = 0
- 2x = 5 ou 3x = 2
x = - 5/2 ou x = 2/3
x = - 2,5
d) (2x +6)(x+1)-6=0
2x² + 2x + 6x + 6 - 6 = 0
2x² + 8x = 0
2x (x + 4) = 0
2x = 0 ou x + 4 = 0
x = 0 ou x = - 4